MENINGKATKAN KUALITAS PEMBELAJARAN DI PEDESAAN MELALUI PERENCANAAN DAN DESAIN PEMBELAJARAN YANG EFEKTIF. - Siti Maisita; Nisa Lathasia (Universitas Islam Syekh Yusuf, 2020)
ABSTRACTQuality is a measure of capacity building activities carried out through various processes in educational institutions. Educational activities can be said to have good quality if the education can produce someone who is able to develop. Quality in learning needs to be considered and studied, because of the influence of the development of globalization which demands the needs of the community every year. The quality of learning in remote areas such as rural areas must be considered because the disparity in the quality of rural education is still low compared to urban areas due to limitations in various aspects, therefore it is necessary to have a good, effective learning planning to improve the quality of education in rural areas Learning planning that becomes a guideline and has been agreed in which there are rules that will run logically systematically. This has been packaged in the educational curriculum at the time of learning, not a projection of the wishes of the teacher unilaterally but the manifestation of several wishes that have been agreed upon for the expected educational goals. The quality of learning in the village requires careful learning planning in the form of management, organizing, formulating learning elements such as objectives, material or content, learning methods and formulating learning evaluations. Learning planning in rural areas must be based on the objectives to be achieved through a needs analysis that is needed in the village and must have targets that are expected to improve the quality of education in the village.KEY WORDS: Quality in Rural Learning, Effective Learning Planning and Design.